Maintenance of p-eIF2α levels by the eIF2B complex is vital for colorectal cancer - Paskov Škapik, Ivana; Giacomelli, Chiara; Hahn, Sarah; Deinlein, Hanna; Gallant, Peter; Diebold, Mathias; Biayna, Josep; Hendricks, Anne; Olimski, Leon; Otto, Christoph; Kastner, Carolin; Wolf, Elmar; et al. (The EMBO journal, 2025)
Protein synthesis is an essential process, deregulated in multiple tumor types showing differential dependence on translation factors compared to untransformed tissue. We show that colorectal cancer (CRC) with loss-of-function mutation in the APC tumor suppressor depends on an oncogenic translation program regulated by the ability to sense phosphorylated eIF2α (p-eIF2α). Despite increased protein synthesis rates following APC loss, eIF2α phosphorylation, typically associated with translation inhibition, is enhanced in CRC. Elevated p-eIF2α, and its proper sensing by the decameric eIF2B complex, are essential to balance translation. Knockdown or mutation of eIF2Bα and eIF2Bδ, two eIF2B subunits responsible for sensing p-eIF2α, impairs CRC viability, demonstrating that the eIF2B/p-eIF2α nexus is vital for CRC. Specifically, the decameric eIF2B linked by two eIF2Bα subunits is critical for translating growth-promoting mRNAs which are induced upon APC loss. Depletion of eIF2Bα in APC-deficient murine and patient-derived organoids establishes a therapeutic window, validating eIF2Bα as a target for clinical intervention. In conclusion, we demonstrate how the expression of the oncogenic signature in CRC is crucially controlled at the translational level.
Gesehen am 19.09.2025